Performance comparison of CNN architectures for detecting Malaria diseases - Rinky, Habiba Karim; Bhuiyan, Rakeya Rahim; Rahman, Humayra Tasnim (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.